Vaccines at Work - Manuel Hoffmann; Roberto Mosquera; Adrian Chadi (Institute of Labor Economics (IZA), 2020)
Influenza vaccination could be a cost-effective way to reduce costs in terms of human lives and productivity losses, but low take-up rates and vaccination unintentionally causing moral hazard may decrease its benefits. We ran a natural field experiment in cooperation with a bank in Ecuador, where we modified its vaccination campaign. Experimentally manipulating incentives to participate in this health intervention allows us to study peer effects with organizational data and to determine the personal consequences of being randomly encouraged to get vaccinated. We find that assigning employees to get vaccinated during the workweek roughly doubled take-up compared to employees assigned to the weekend, which indicates that reducing opportunity costs plays an important role in increasing vaccination rates. Coworker take-up also increased individual take-up significantly and is driven by social norms. Contrary to the company's expectation, vaccination did not reduce sickness absence during the flu season. Getting vaccinated was ineffective with no measurable health externalities from coworker vaccination. We rule out meaningful individual health effects when considering several thresholds of expected vaccine effectiveness. Using a dataset of administrative records on medical diagnoses and employee surveys, we find evidence consistent with vaccination causing moral hazard, which could decrease the effectiveness of vaccination.
Keywords: D90; I12; J01; N36; 330; health intervention; flu vaccination; sickness-related absence; field experiment; random encouragement design; moral hazard; technology adoption